The Effect of Coping Strategies on work Stress among Tile Factory workers in Abadeh - Ali NEMATOLAHI; Hamideh MIHANPOUR; Zahra MANSOURI (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Stress is result of an interaction between an individual and a situation in which the person cannot meet the demands which is a common problem in work environments. The aim of this study was to investigate the effect of coping strategies on work stress among tile factory workers in Abadeh. Methods: This descriptive-analytic study was carried out on 288 people selected by systematic randomized stratified sampling method from workers of three active tile factories in Abadeh city in 2015. Samples were evaluated using Hellriegel & Slocum’s work stress questionnaire and Coping Inventory for Stressful Situation (CISS) questionnaire. The data were evaluated using multiple regression analysis. Results: The results showed that problem-focused coping with the beta coefficient (β = 0.320) and the significant level (P = 0.0005) were negative predictors and emotion-focused coping with beta coefficient (β = 0.329) and the significance level (P = 0.0005) were positive predictors of work stress. . The emotion-focused coping was also able to predict the changes related to work stress and its dimensions. However, avoidance-focus coping was not able to predict work stress and its dimensions. Conclusion: According to the findings, the effects of work stress of workers can be improved by increasing problem-focused strategies through training the use of these types of coping strategies and also reducing their emotion-focused coping.